The Role of Islamic Educational Management in Realizing Effective School Governance: A Narrative Literature Review - Samsu; Try Susanti; Latansa Hafizotun; Nurul Annisa Dewantari Nasution (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
This narrative literature review aims to critically examine the role of Islamic Education Management (MPI) in realizing effective school governance and to propose an integrative framework bridging Islamic values with contemporary evidence-based effectiveness indicators. Unlike previous reviews that predominantly focus on the normative theological foundations of MPI or treat school governance through a purely secular lens, this study offers a novel conceptual contribution by operationalizing abstract Islamic principles into a concrete, multidimensional governance model. Employing a narrative synthesis of peer-reviewed literature from 2020 to 2026, the study analyzes how core MPI values—syura, amanah, ‘adl, and ihsan—intersect with fundamental management functions. The results indicate that MPI transcends conventional administrative models by embedding spiritual accountability, participatory decision-making, equitable resource distribution, and continuous excellence into institutional practices, thereby enhancing stakeholder trust and organizational climate. However, the synthesis also identifies critical implementation barriers, including financial constraints, regulatory tensions, and human resource gaps, which necessitate deliberate leadership commitment and contextual adaptation. The study concludes that MPI functions not merely as an ethical overlay, but as a holistic governance paradigm capable of harmonizing modern educational standards with Islamic epistemological foundations. Ultimately, this review provides an actionable conceptual framework for policymakers and school leaders to cultivate ethically grounded, high-performing educational environments, effectively bridging the critical gap between faith-based values and empirical school governance.